Usul Fiqih dan Tipologi Penelitian Hukum Islam - Muhammad Al Faruq (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2020)
In general, the proposal of jurisprudence is a method of studying Islam in general and in the history of Islamic culture this is the only typical Islamic method that developed, but in a special sense, the proposal of fiqh is a method of discovery of shari'a law. As a method of legal discovery, the proposal of jurisprudence is part of the research method of Islamic law in general. Islamic law research as a whole is distinguished into two major areas, namely descriptive Islamic law research and prescriptive Islamic law research. Descriptive Islamic law research sees Islamic law as a social phenomenon that interacts with other social symptoms. In this connection Islamic law can be seen both as an independent variable (free) that affects society and as a dependent variable (bound) that is influenced by society.